Mobilidade ocupacional no Brasil: uma análise das chances de mobilidade e inserção ocupacional segundo a origem, a cor e a situação de migração e não-migração para homens chefes do domicílio (1988-1996) - Lygia Gonçalves Costa (Universidade do Vale do Rio dos Sinos (UNISINOS), 2009)
Our goal in this article is twofold. Firstly, we present a short overview of theoretical and empirical studies about social stratification and mobility in Brazil. Secondly, we analyze mobility and occupational insertion chances according to origin, color and various migrational status such as migrants from the Northeast Region to the Southeast Region, non-migrants from the Northeast Region and non-migrants from the Southeast Region. The Logit Multinomial model is used for the hypothesis test where the relative chances for occupational insertion of the various migration groups were analyzed. We use the same occupational classes as the ones used by Erikson, Goldthorpe and Portocarrero (EGP) (Erikson et al., 1979), also the same as in the classical mobility study 'The Constant Flux' (Erikson and Goldthorpe, 1993), only adapting the self-employed category to the Brazilian reality. By the lack of recent data we only analyze the last two editions of the "National Sample Survey of Households" (Pesquisa Nacional por Amostra de Domicílios - PNAD/IBGE 1988 and 1996).